Semen and reproductive parameters during some abstinence periods after cigarette smoke exposure in male rats - Sankako, Michele Kimie [UNESP]; Garcia, Patricia Carvalho [UNESP]; Piffer, Renata Carolina [UNESP]; Pereira, Oduvaldo Câmara Marques [UNESP] (Brazilian Archives of Biology and Technology, 2013)
Cigarette smoking is very widespread globally and can also be implicated in male and female infertility. This study aimed to evaluate the testicular function throughout a complete spermatic cycle during abstinence from cigarette smoke exposure in order to identify a possible residual damage and whether the parameters could recover spontaneously. Male Wistar rats were randomly divided into control and cigarette smoke-exposed (20 cigarettes/day/2 months) groups. After finishing the treatment, according to the number of days after the last cigarette exposure (0, 15, 30, or 60 days), the rats were euthanized and analyzed for compromised sperm count and quality. Results showed residual damage on sperm concentration, motility and morphology; the recovery of these parameters occurred only at 60th days of abstinence. The study showed that cigarette smoke exposure damaged the semen and reproductive parameters and that the spontaneous recovery of some parameters occurred only after a complete spermatic cycle subsequent to stopping smoke exposure.
Keywords: Cigarette; Semen; Spermatozoa; Testicular Function; Male Rat